﻿Nitric oxide-mediated effects of L-ornithine-L-aspartate in acute toxic liver injury - Vitalij Datsko; Halyna Loi; Tamara Datsko; Alla Mudra; Anna Mykolenko; Tetyana Golovata; Mykhailo Furdela; Yurii Orel; Iryna Smachylo; Andrii Burak; Mykola Klantsa; Oleksandra Oleshchuk (Pensoft Publishers, 2022)
This study was aimed to investigate nitric oxide-dependent mechanisms of L-ornithine-L-aspartate (LOLA) action in acute toxic liver injury in rats. Acute hepatitis was induced in Wistar rats using 50% oil solution of tetrachloromethane (CCl4) intragastrically (2 g/kg) twice in a 24 hour interval. Intraperitoneal treatment with LOLA (200 mg/kg) was started 6 hours after the second CCl4 administration and maintained for 3 consecutive days. L-Nω-Nitroarginine Methyl Ester (L-NAME) was used intraperitoneally (10 mg/kg). In CCl4-induced hepatitis, LOLA restores the structure of hepatocytes and prevents aminotransferases, alkaline phosphatase and gamma-glutamyl transferase elevation. It decreases total bilirubin concentration but does not affect increased cholesterol level. LOLA augments urea concentration, total protein level in blood and liver as well as serum and liver content of nitrite anions. LOLA enhances activity of catalase, glutathione S-transferase, manganese superoxide dismutase, increases reduced glutathione level and total antioxidant capacity and decreases thiobarbituric acid reactive substances level. The concomitant use of L-NAME inhibits the action of LOLA to enhance nitrite anions synthesis both in serum and liver, to delay the recovery of hepatocytes, to counteract LOLA effect against blood total protein reduction, to prevent the decline in aminotransferases, alkaline phosphatase,, gamma-glutamyl transferase and glutathione S-transferase activity and to reduce catalase activity and reduced glutathione level. Therefore, in CCl4-induced hepatitis, LOLA effectively prevents cytolysis and cholestasis, improves liver metabolism and protects against oxidative stress. Partially, these changes occur in nitric oxide-mediated mechanism since the use of L-NAME declines most of LOLA effects.